Społeczno-ekonomiczne predyktory poglądów kobiet i mężczyzn dotyczących kulturowych ról płci w Polsce - Kocot-Górecka, Katarzyna (Studia Demograficzne, 2014)
Fertility decline in developed countries over recent five decades and persisting low fertility in the remarkable number of countries are increasingly attributed to changing gender roles, particularly to incompatibilities between institutional adjustments of individual- and family- oriented institutions as well as within the family and changing perceptions on social roles of women and men. These arguments are voiced also when debating on low fertility in Poland. The article focuses on perceptions of gender roles and their diversity across population groups which differ by socio-demographic attributes. Additionally, possible influences of parental home on opinions about gender roles are accounted for. The data coming from the Generations and Gender Survey, carried out in Poland in 2010/2011, made it possible to define two synthetic variables which described attitudes towards gender equality in the social sphere and in the private sphere (a responsibility for a child). Descriptive results confirmed findings of other studies: the gender attitudes are more diversified among women than men, especially as regards gender equality in the social sphere, women show more egalitarian attitudes than men, and within an age increase a social approval for gender equality declines. The generalized linear mixed models of two synthetic gender variables were used to identify predictors of gender attitudes across two birth cohorts of women and men – those born either in the years 1950–1969 or in the years 1970–1989. Among individual characteristics education, religiosity and place of residence were found out – as expected – the main predictors of gender attitudes. Contrary to expectations, labour market status, marital status and a number of children did not always play a significant role for distinguished cohorts of men and women. Economic activity showed its impact on women’s gender attitudes only. There are also some signs that in the 1970–1989 cohorts younger people are less in favour of gender equality than those over 30 years of age. Parental home attributes (place of residence at age 15, mother’ education and mother’s economic acitivity, number of siblings, and religiosity) were displayed as relevant predictors of gender attitudes for both birth cohorts of men and women.